Crip Time and Radical Care in/as Artful Politics - May Chazan (Social Sciences, 2023)
This article brings together critical disability scholarship and personal narrative, sharing the author’s pandemic story of disruption, caregiving, grief, burnout, cancer, and post-operative fatigue. It offers critical reflection on the limits of the neoliberal academy and possibilities for practicing liberatory politics within it, posing two central questions: What does it mean to crip time and centre care as an arts-based researcher? What might a commitment to honouring crip time based on radical care do for the author and their scholarship, and for others aspiring to conduct reworlding research? This analysis suggests that while committing to “slow scholarship” is a form of resistance to ableist capitalist and colonial pressures within the academy, slowness alone does not sufficiently crip research processes. Crip time, by contrast, involves multiply enfolded temporalities imposed upon (and reclaimed by) many researchers, particularly those living with disabilities and/or chronic illness. The article concludes that researchers can commit to recognizing crip time, valuing it, and caring for those living through it, including themselves, not only/necessarily by slowing down. Indeed, they can also carry out this work by actively imagining the crip futures they are striving to make along any/all trajectories and temporalities. This means simultaneously transforming academic institutions, refusing internalized pressures, reclaiming interdependence, and valuing all care work in whatever time it takes.